Food production from livestock in small farm systems for urban populations in South East Asia - Devendra, C. (World Association for Animal Production, 1995)
Food production from livestock in small farm systems for urban populations is discussed in the context of projected human population increase, market-led demand, rising incomes, and changing consumer preferences. These will accelerate the demand for food in the future and access to it, which in turn, will place considerable pressures on the use of natural resources (land, crops and animals). Technological and socio-economic factors are the key determinants that will drive components of the animal industries. The South East Asian region has a diversity of ruminant and non-ruminant animals approximating to between 2-11 percent and 10-25 percent respectively of the total animal resources in Asia. Over the period 1981-1993, the annual rate of growth of the buffalo population was on the decline, however, cattle grew at 2.8 percent, and small ruminant -3.7 percent per year. The chicken population had the highest growth rate of 10.6 percent per year. The demand projections for meat, milk and eggs in Asia suggest the need for a two to three-fold increase in present supplies for the year 2006. Good prospects exist for interregional trade and therefore the Development of livestock. The prerequisites for these are efficient production systems and low production costs in order to make available animal products within reach of consumers purchasing power, and benefit from this trade. The extent of the contribution of small farm systems to the supply of foods of foods of livestock origin is uncertain, but is considerable. This associated with the relatively large concentrations of both ruminants and non-ruminants in these small farms. Increasing productivity from livestock necessitates more complete utilization of The totality of the animal genetic resources (ruminants and non-ruminants) and widespread use of the available technologies and more prerequisites for these include interdisciplinarity, strong systems orientation, concerted on-farm application, and evaluation of impact.